Terrorists on trial : a performative perspective - Graaf, Beatrice de; Schmid, Alex P. (Alex Peter), 1943- (UPCC book collections on Project MUSE. Political Science and Policy Studies., 2016)
"This volume views terrorism trials as a form of theatre, where the 'show' that a trial may offer can develop often unexpected dynamics, which at times might inconvenience the government. Seeing terrorism trials as a stage where legal instruments are used (and abused) to argue the validity of contested political constructs, this study presents a performative perspective to draw attention to the mechanisms and effects of terrorism trials in and outside the courtroom. With a special focus on how the power of these performances may in turn shape new narratives of justice and/or injustice, it offers vital insights into terrorism trials directed involving different types of terrorism suspects, from left-wing to ethno-nationalist and jihadist terrorists, in Spain, Russia, Germany, the Netherlands, and the United States"--Back cover